Immune changes: 2 h of continuous vs. intermittent cycling - Nieman, D.; Henson, D.; Gojanovich, G.; Davis, J. M.; Dumke, C.; Utter, A.; Murphy, A.; Pearce, S.; McAnulty, S.; McAnulty, L. (International Journal of Sports Medicine, 2007)
Immune changes following 2 h of intensive cycling with or without rest intervals were measured in trained cyclists (n = 12) who functioned as their own controls during two test sessions that were separated by two weeks. Subjects cycled for 2.0 h at ~ 64 % Wattsmax continuously (C) or with 3-min rest intervals (R) interspersed every 10 min (2.6 h total time), with the order of the sessions randomized. Blood samples were collected 30-min pre-exercise, and immediately and 1-h postexercise, and assayed for blood leukocyte subset counts, plasma IL-6, IL-10, IL-1ra, IL-8, PHA-induced lymphocyte proliferation, and natural killer cell activity (NKCA). Significant time effects were measured for all immune measures, but no significant differences in the pattern of change were found between C and R exercise trials. In conclusion, immune changes induced by 2 h of intense and prolonged exercise paralleled those measured when athletes rested 3 min every 10 min of exercise.